Interactions between Natural and Synthetic Organics in the Coagulation Process - Diamadopoulos, Evangelos (My University, 1984)
The removal of fulvic acid, the most soluble fraction of humic matter, with aluminum and polyacrylamide was investigated. The experimental conditions were similar to those usually encountered in practice. The pH ranged from 6 to 8, the aluminum dosage from 10ˉ⁵M to 0.5 x 10ˉ³ M, and the polymer concentration from 0 to 1 mg/L. The fulvic acid concentration was constant at 10 mg/L.
The removal of fulvic acid with aluminum was found to depend on the particle size of the aluminum-fulvic acid flocs. This was demonstrated by both the increased removals when filters with a pore size of 0.10 μm were used (as opposed to filters with a pore size of 0.45 μm) and the beneficial effect of the presence of nonionic polyacrylamide. The nonionic polymer promoted both the removal after settling and the removal after filtration. The latter was attributed to the flocculation of micro-colloidal particles which in the absence of the polymer passed through the pores of the filter.
Based on a three-level factorial experimental design an empirical statistical model of the removal of fulvic acid was developed. The model was based on the consideration that for a narrow operating region, the response surface may be approximated with a quadratic mathematical expression. By applying this technique the effect of the pH, aluminum dosage and polymer dosage were quantitatively modelled. A polymer dosage of 0.1 mg/L was found to be optimal because it gave the minimum cost of chemicals, for the desired high degree of removal.
Finally, the most significant factors that affected the removal of fulvic acid with aluminum, in addition to the pH, the aluminum dosage and the polymer dosage, were the calcium present in the water and the interaction of calcium with the pH. The effect of calcium was larger at pH 8 than at pH 7. The effect of the polymer properties was not as large as the effect of the calcium, with the effect of the polymer molar mass being more important than the effect of the degree of hydrolysis of the polyacrylamide.
Keywords: Chemical Engineering; Chemical Engineering